2021
DOI: 10.1186/s43058-021-00133-w
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative chronic care model implementation within outpatient behavioral health care teams: qualitative results from a multisite trial using implementation facilitation

Abstract: Background This paper reports on a qualitative evaluation of a hybrid type II stepped-wedge, cluster randomized trial using implementation facilitation to implement team-based care in the form of the collaborative chronic care model (CCM) in interdisciplinary outpatient mental health teams. The objective of this analysis is to compare the alignment of sites’ clinical processes with the CCM elements at baseline (time 1) and after 12 months of implementation facilitation (time 2) from the perspec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…For organizational barriers, Facilitation-based on the integrated-Promoting Action on Research Implementation in Health Services (i-PARIHS) [39] frameworkprovides schools with ongoing consultation from an expert in strategic thinking and EBP implementation to garner administrative support, solve logistical challenges, and build community buy-in. In several communitybased cluster-randomized trials, Facilitation has been shown to improve mental health EBP uptake [30,34,[40][41][42][43][44][45] and to be highly cost-effective [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…For organizational barriers, Facilitation-based on the integrated-Promoting Action on Research Implementation in Health Services (i-PARIHS) [39] frameworkprovides schools with ongoing consultation from an expert in strategic thinking and EBP implementation to garner administrative support, solve logistical challenges, and build community buy-in. In several communitybased cluster-randomized trials, Facilitation has been shown to improve mental health EBP uptake [30,34,[40][41][42][43][44][45] and to be highly cost-effective [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…They then summarized coded text by relevant subcodes for the four i-PARIHS constructs in a Word document. Because they had previously coded the same dataset by collaborative care model elements [ 42 ], they also examined the cross-coding between the collaborative care model and i-PARIHS codes/subcodes. The analysis team included JLS, KLD, and another BH QUERI investigator who had served on the expert panel.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with other qualitative work (Hamilton & Finley, 2019;Miller et al, 2019;Sullivan et al, 2021), we aimed to recruit about three to four staff at each of the nine VA medical centers, including a multidisciplinary mix of mental health leaders and frontline BHIP staff. Whenever possible, for each site we aimed to recruit at least one BHIP clinician who had been present during the original BHIP-CCM Enhancement Project (i.e., had participated in implementation facilitation between 2016 and 2018).…”
Section: Sampling Approachmentioning
confidence: 99%
“…We developed the interview guide collaboratively as a project team, based on the following: (a) the six CCM elements, (b) core constructs of the i-PARIHS implementation framework (Harvey & Kitson, 2015;Ritchie et al, 2022), (c) the current project's focus on sustainability, and (d) the interview guides used in previous studies of BHIP-CCM implementation (Miller et al, 2019;Sullivan et al, 2021;see Supplemental File). Interview questions asked about the extent to which care processes within the BHIP team remained aligned with the 6 CCM elements described above.…”
Section: Data Collectionmentioning
confidence: 99%